Proses Berpikir Siswa SD dalam Menyelesaikan Masalah pada Materi Pecahan - siti faridah; Ratna Nulinnaja (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to explain how elementary school students carry out their thinking processes to be able to solve problems in fractional material in fifth grade students of SDN Harjokuncaran 03 Sumbermanjing wetan Malang who have studied fractions. Data is obtained through the Think-Out-Loud (TOL) method or often called Think Aloud. In the TOL method, students are expected to be able to think critically and express in solving the problems obtained. The results of the study, students' thinking processes in solving problems, were taken by giving two fractional problems to each subject, namely 2 high-ability subjects (S1.1 and S1.2), 2 moderately capable subjects (S2.1 and S.2). ) and 2 subjects with low ability (S3.1 and S.3.1). After collecting data and analyzing it, the researcher can conclude that this study describes how the thinking process of elementary school students in solving problems that refers to Polya, including: (1) students can understand the problems obtained then identify sentences in the form of statements and question sentences then they are expected to be able to perform variable assumptions; (2) able to plan and be able to make appropriate solutions relying on the assumptions of variables, symbols, equations, and mathematical models; (3) elementary school students are able to participate in planning and problem solving by means of elementary students solving equations using algebraic properties and substitution; and (4) elementary students are able to review again by matching the results obtained with what is already known. Keywords: Thinking Process, Problem Solving, Fractions.